2017
DOI: 10.1108/rpj-02-2016-0020
|View full text |Cite
|
Sign up to set email alerts
|

Edge quality in fused deposition modeling: I. Definition and analysis

Abstract: Purpose-To discuss the problem of the geometric accuracy of edges in parts manufactured by the FDM process, as a preliminary step for an experimental investigation. Design/methodology/approach-Three geometric variables (inclination, included and incidence angle) were defined for an edge. The influence of each variable on the geometric errors was explained with reference to specific causes related to physical phenomena and process constraints. Findings-Occurrence conditions for all causes were determined and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…Results showed a close relationship between surface finish, with build direction. Armillotta and Cavallaro (2017) proposed an empirical model to forecast the existence of visible imperfections on the edges of a part before manufacturing it with a given build orientation (Armillotta et al , 2017a). Alsoufi and Elsayed (2017) investigated the influence of factors on the surface finish of parts made up of PLA+ material and found that layer height and nozzle diameter were significant in terms of part surface roughness.…”
Section: Fused Deposition Modelling Part Quality and Performance Improvementmentioning
confidence: 99%
“…Results showed a close relationship between surface finish, with build direction. Armillotta and Cavallaro (2017) proposed an empirical model to forecast the existence of visible imperfections on the edges of a part before manufacturing it with a given build orientation (Armillotta et al , 2017a). Alsoufi and Elsayed (2017) investigated the influence of factors on the surface finish of parts made up of PLA+ material and found that layer height and nozzle diameter were significant in terms of part surface roughness.…”
Section: Fused Deposition Modelling Part Quality and Performance Improvementmentioning
confidence: 99%
“…Therefore, the positioning of the component in the building space is an important process parameter regarding to the surface quality of the finished part, as all edges of the part that are not oriented parallel or perpendicular to the building platform, will show a more or less pronounced staircase effect [30]. ARMILLOTTA et al [75], therefore, develop an improved calculation model to predict the surface quality more precise, depending on the position of the component in the building space. This model can be used to reduce the staircase effect and improve the surface quality.…”
Section: Flat Slicing Methodsmentioning
confidence: 99%
“…These artifacts cannot be well described with existing quality metrics for FDM, like (global) geometric accuracy and/or surface roughness (i.e. [21,22]), both which do not capture the effect of the geometric variation on the perceived gray scale. Even though the sagging of vertical surfaces is employed within the range of 0.2 mm, we found the human eye can easily detect these inaccuracies, especially in regions with a uniform gray scale.…”
Section: Visual Artifactsmentioning
confidence: 99%